Selective and clean synthesis of aminoalkyl-H-phosphinic acids from hypophosphorous acid by phospha-Mannich reaction - Urbanovský, Peter; Kotek, Jan; Císařová, Ivana; Hermann, Petr (RSC advances, 2020)
Aminoalkyl-H-phosphinic acids, also called aminoalkylphosphonous acids, are investigated as biologically active analogues of carboxylic amino acids and/or as valuable intermediates for synthesis of other aminoalkylphosphorus acids. Their synthesis has been mostly accomplished by phospha-Mannich reaction of a P-H precursor, an aldehyde and an amine. The reaction is rarely clean and high-yielding. Here, reaction of H3PO2 with secondary amines and formaldehyde in wet AcOH led to aminomethyl-H-phosphinic acids in nearly quantitative yields and with almost no by-products. Surprisingly, the reaction outcome depended on the basicity of the amines. Amines with pK a > 7-8 gave the desired products. For less basic amines, reductive N-methylation coupled with oxidation of H3PO2 to H3PO3 became a relevant side reaction. Primary amines reacted less clearly and amino-bis(methyl-H-phosphinic acids) were obtained only for very basic amines. Reaction yields with higher aldehydes were lower. Unique carboxylic-phosphinic-phosphonic acids as well as poly(H-phosphinic acids) derived from polyamines were obtained. Synthetic usefulness of the aminoalkyl-H-phosphinic was illustrated in P-H bond oxidation and its addition to double bonds, and in selective amine deprotection. Compounds with an ethylene-diamine fragment, e.g. most common polyazamacrocycles, are not suitable substrates. The X-ray solid-state structures of seventeen aminoalkyl-phosphinic acids were determined. In the reaction mechanism, N-hydroxyalkyl species R2NCH2OH and [R2N(CH2OH)2]+, probably stabilized as acetate esters, are suggested as the reactive intermediates. This mechanism is an alternative one to the known phospha-Mannich reaction mechanisms. The conditions can be utilized in syntheses of various aminoalkylphosphorus compounds.